Net buying pressure and informed trading in the options market: Evidence from earnings announcements - Ihsan Ullah Badshah; Hardjo Koerniadi (Journal of Risk and Financial Management, 2022)
By employing the modified net buying pressure as a measure of informed option trading, this study tested whether option trading around quarterly earnings announcements is either directionally motivated and/or volatility motivated. We found evidence that is consistent with the idea that option investors have private information prior to positive earnings announcements and use at-the-money options to exploit their informational advantage. In the post-event period, however, informed option investors trade by using deep-out-of-the-money and out-of-the-money options. We documented limited evidence on the volatility-motivated option trading, and our results suggest that this type of option trading could be motivated by hedging purposes only.
Keywords: G10; G13; G14; 330; earnings; announcements; options; informed trading; net buying pressure; volatility; direction; at-the-money; out-of-the-money; deep-out-of-the-money